Identification of High-Mobility Group Box 1 (HMGB1) Expression as a Potential Predictor of Rejection and Poor Prognosis After Liver Transplantation - Ye, Zhou (Ann Transplant, 2021)
BACKGROUND: Acute cellular rejection (ACR) frequently occurs after liver transplantation (LT) and can result in permanent damage of the liver allograft. Specific and sensitive biomarkers for predicting and monitoring ACR are vital for guiding post-transplantation care. In the present study, we aimed to investigate the function of high-mobility group box 1 (HMGB1) in predicting ACR and prognosis after LT. MATERIAL/METHODS: A total of 113 LT recipients were enrolled in the study, including 62 patients in an ACR group and 51 patients in a non-rejection group. Using tissues from the 113 patients, HMGB1 expression was examined by immunohistochemistry, and the total score for HMGB1 expression was calculated by multiplying the percentage of immunoreactive cells score and the staining intensity score. We then analyzed the association between HMGB1 expression and clinical features. Finally, the function of HMGB1 in predicting the prognosis of LT was determined using Kaplan-Meier (K-M) survival and Cox multivariate analyses. RESULTS: Immunohistochemical staining results demonstrated that the expression of HMGB1 was significantly increased in the ACR group, compared with that in the non-rejection group (P<0.05). Clinical characteristic analysis revealed that high HMGB1 levels were related to ACR (P<0.05). Moreover, K-M survival analysis showed that patients with high HMGB1 expression displayed poorer prognosis (P<0.05). Cox multivariate analysis demonstrated that HMGB1 was an independent prognostic predictor for post-LT survival (odds ratio, 3.283; P=0.008). CONCLUSIONS: LT recipients’ HMGB1 levels may be a useful and noninvasive biomarker for the prediction of ACR and prognosis after LT.